(untitled) (Praxis Educativa, 2020)
The objective of this work is to draw a series of coordinates from which to reflect on the pedagogical task that we carry out from the Extension Program in Prisons (FFyL / UBA) in its connection with Comprehensive Sex Education, through presentation, exploration and characterization of certain “ESI scenes” in confinement contexts. For this, I propose in general lines some training axes of the ESI with its possible ways of linking, tension and articulation with cis women and transdeprived of liberty in CPF IV, located in the town of Ezeiza. One of the purposes is to pay for the deployment of non-punitive imaginations anchored in the body, rights and pleasure, in pedagogical political praxis. And above all, endow the university experience with new meanings, which in our specific interventions, moves, disrupts and transcends the academic proposal.